Open Educational Resources as the Third Pillar in Project-Based Learning During COVID-19: The Case of #dariahTeach - Papadopoulos, Costas; Rasterhoff, Claartje; Schreibman, Susan (KULA)

(untitled) (University of Victoria Libraries, 2022)
Teaching in higher education in the Netherlands was affected, as in most other parts of the world, due to the COVID-19 pandemic. This paper reflects on how two courses were taught and experienced by students during the 2020–21 academic year in the MA Media Studies: Digital Cultures at Maastricht University. It particularly focuses on how the integration of open educational resources into the course design, what we call a third pedagogic pillar, contributed to the success of the two courses and students’ positive learning experience.